Pathology Quiz Case: Plasmacytoid Dendritic Cell Neoplasm - Quinn A. Dunlap B.S.; Kristine E. Day M.D.; Samuel G. Borak M.D.; Bradford A. Woodworth M.D. (Allergy & Rhinology, 2014)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematologic malignancy that possesses a heterogenous clinical and immunophenotypic presentation. The current case report describes an interesting and unique presentation of BPDCN as a primary paranasal sinus tumor without evidence of cutaneous or systemic involvement. As such, the report further contributes to the ongoing debate regarding the true putative origin of the neoplasm, as well as highlights the optimal diagnostic modalities, paramount importance of early diagnosis, and vast heterogeneity exhibited by this fascinating malignancy. The atypical presentation described here indicates the manifestations of BPDCN are more heterogenous than previously documented and thus can not be definitively ruled out in the absence of bone marrow, peripheral blood, or cutaneous involvement. Furthermore, atypical neoplastic presentations mandate flow cytometry and adjunctive immunohistochemistry for the definitive diagnosis of BPDCN, and early diagnosis of such neoplasms are critical for rapid initiation of treatment and improved outcomes.